The dimensions of praise - Kreitlow, William Fabrício; Stange, Klaus Andreas (Vox Scripturae - Revista Teológica Internacional, 2017)
What is the right way to praise God? Is praise limited to musicality? Would not the praise of God be something far more encompassing than a single form? To find answers deepened the research in the theme through the analysis of Greek and Hebrew words used in the Bible as synonyms for praise. The Hebrew words llh (Hālal), hdy (Yādâ), wr (Rûm), rmz (Zāmar) e rb (Bārak) were analyzed, as well as the Greek words ai``ne,w (Aineō), o``mologe,w (Homologeō) e eu``loge,w (Eulogeō). Throughout the study a pattern was observed in the act of praising: (1) God acts mightily in favor of his people; (2) the people respond with gratitude and praise; (3) God accepts the acts of worship of his people. According to this cycle and with the analysis of the words one can see that praise is recognition of the divinity and sovereignty of God as it is also recognition of human finitude and sinfulness. In Leviticus 7.12-15, the sacrifice of praise is described, where the offerer made declarations of exaltation to God and confessed his sins. Historically, praise as music was instituted by King David. He was the first to appoint Levites and priests to minister continually before the ark of the Lord with music and song. David’s instructions were followed by Solomon, rescued by Hezekiah, and later canonized by the post-exilic community. As a practical impetus, this article asks whether contemporary praise in Brazilian Protestantism has been realized in such a way that the aim is the aggrandizement of God and not human approval.